2012
DOI: 10.1002/pon.3105
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial needs of cancer patients and related factors: a multi‐center, cross‐sectional study in Korea

Abstract: Unmet psychosocial needs were common in cancer patients and have varied according to patients' socio-demographic and clinical factors. These results suggest that a psychosocial approach to treatment should be applied comprehensively and that such an approach should be matched to patients' socio-demographic and clinical circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
5
6
0
Order By: Relevance
“…McIllmurray et al (2001) reported that the participants of lower socioeconomic status have significantly higher levels of need, although this was minimal (23%) in participants as a whole, thus supporting the result of this study. This is consistent with Choi et al (2013), who reported economic support as the greatest social support need for people with cancer in Korea. This suggests that financial support for people with cancer, whether their income is high or low, is especially important in Korea.…”
Section: Variablesupporting
confidence: 93%
See 3 more Smart Citations
“…McIllmurray et al (2001) reported that the participants of lower socioeconomic status have significantly higher levels of need, although this was minimal (23%) in participants as a whole, thus supporting the result of this study. This is consistent with Choi et al (2013), who reported economic support as the greatest social support need for people with cancer in Korea. This suggests that financial support for people with cancer, whether their income is high or low, is especially important in Korea.…”
Section: Variablesupporting
confidence: 93%
“…This was connected with marital status which ranked as the second predictive factor. This is consistent with the studies (Choi et al, 2013;Ha and Song, 2013) showing that people with cancer or other disease who live alone reported a greater need for help with loneliness or feeling of isolation. Therefore, oncology nurses need to include the opportunity to share suffering feelings in delivering interventions (Yi et al, 2011).…”
Section: Significant Unmet Psychosocial Needssupporting
confidence: 92%
See 2 more Smart Citations
“…Adverse psychosocial effects are associated with unfulfilled psychosocial requirements [8]. On this subject, Choi et al described the importance of being given sufficient information [9]. According to Maslowʼs "A theory of human motivation", human needs are ordered in the following hierarchical structure: Physiology (highest), safety, love and self-realisation.…”
Section: Zusammenfassungmentioning
confidence: 99%